PARTISIPASI MASYARAKAT DALAM PEMBAYARAN PAJAK BUMI DAN BANGUNAN (Studi Di Desa Pungguk Pedaro Kec. Bingin Kuning Kab. Lebong) - Daya Dinda Sari; Titi Darmi; Ju’im (Jurnal Cakrawala Ilmiah, 2021)
The success of a country is a society that is willing to participate in paying land and building taxes and that is one of the supporting factors, the awareness and sense of participation that must be present in every community to support all development activities both at the regional and central level. if the community does not pay taxes then they will not be good Indonesian citizens. Therefore, the need for public participation. The formulation of the problem in this study is to find out how the action of community participation in the payment of Land and Building Tax (PBB) in Pungguk Pedaro Village, Bingin Kuning District, Lebong Regency. The purpose of this study was to determine and analyze the level of community participation in land and building tax payers in Pungguk Pedaro Village, Bingin Kuning District, Lebong Regency. In this study, researchers used qualitative descriptive research motedo with data collection techniques through observation, interview and documentation techniques